MULTIMODAL COMPOSITION AS POTENTIAL SUBSTITUTION OF CONVENTIONAL WRITING TASKS FOR ESP STUDENTS - Kondrashova, Alla (European Science, 2024)
In today’s world of ESP education, multimodal composition, which combines different types of media and communication formats, is becoming increasingly important. This article explores the impact of multimodal writing on ESP students’ learning, focusing on